Triple Helix Model in Developing Technological Innovation: The Case of Computer Based Interlocking - Nurzal, Erry Ricardo; Waluyo, Marhaindro (The Asian Journal of Technology Management (AJTM), 2012)
Computer Based Interlocking (CBI) is the most important part of the electric railway signalingsystem which serves as the â€œbrainâ€ that controls the operation of electrical signaling system thatreplaces the role of the electromagnetic relay which has gradually been abandoned. Developmentof CBI is based on the fact that until recently the signaling system in Indonesia is still reliedheavily on the CBI products from foreign vendors. Therefore, the development of domestic CBIproducts is really necessary in order to decrease the dependence on technology from foreignvendors that at the same time is also be able to support the accelerated development of railwayinfrastructure in Indonesia.The CBI development is conducted in the form of a collaboration involving the government,universities, and industry. This paper explores and analyzes the roles and interactions betweendifferent actors in the triple helix perspective, and identifies how the innovation ecosystemfunctioning with support from the government.Based on the data collected through in-depth interview with the actors involved in the CBI casestudy, this paper gives some key findings. First, government role is very important in establishingan innovation ecosystem for CBI development. Second, the leader in the development of CBItechnological innovation should be the industry supported by governmental R & D institutionsand universities. Third, R & D consortium is an effective vehicle for creating an interactionamong industry, academia, and government.Such findings may provide conceptual direction which is important for the development oftechnological innovation in Indonesia. In addition, in providing support for R&D activities, thegovernment needs to direct its R & D incentives to the industry as a business practitioner with itsown technology roadmap. The possible further research may include some research issues. First,is the pattern occurred in the CBI case also applied in the other cases of technological innovationdevelopment? Second, what obstacles can be identified in the development of CBI technologicalinnovation capabilities? Third, what is the impact of research collaboration in the development ofCBI technological innovation? Keywords :Indonesia, R & D Consortium, Industrial Research, Government Support